Helix Project: Exploring the Social Internet of Things (SIoT) in Care of Blind People - Haertel, Felipe; Camargo, Leandro; Lopes, João; Pernas, Ana; Mota, Fernanda; Barbosa, Jorge; Yamin, Adenauer (Journal of the Brazilian Computer Society, 2022)
The wide variety of available mobile devices, associated with the increase in wireless communication network availability, enables an increasing offer of mobile and ubiquitous technologies. In this sense, this article proposes an approach called Helix-SIoT, which explores the Social Internet of Things concepts to support Blind People (BP). The objective is to enhance the treatment of the different sensors that integrate the assistance of these people with SIoT use. For this, the proposal employs Context Awareness and Multiple Criteria Decision Analysis, helping people’s autonomy in terms of mobility, response times, and the choice of the Caregiver in the most transparent way possible. The functional architecture of the Helix approach operates integrated with the Adaptation and Context Recognition Subsystem of the EXEHDA middleware, which provides support for the acquisition, storage, and processing of context information used by the mobile Helix-SIoT applications.